Reversible cytotoxic lesion of the corpus callosum as a radiological finding in idiopathic intracranial hypertension and its association with disease management - Abdelmonem M. Hassan; Mohie-eldin Tharwat Mohamed; Ahmed S. Aly; Ali Mahmoud Ahmed (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Cytotoxic lesion of the corpus callosum (CLOCC) is a magnetic resonant image (MRI) finding that could be triggered by anti-seizure medications, viral encephalitis, malignancies, metabolic disturbances, altitude sickness and migraine with aura. Its association with the cerebrospinal fluid (CSF) pressure or volume is not established. Case presentation A 22-year-old female patient presented with a headache with features suggestive of idiopathic intracranial hypertension (IIH). The MRI head revealed CLOCC as a rounded lesion in the splenium of the CC with restricted diffusion. The CSF pressure was 26 cmH2O, and its analysis showed only a mild increase in mononuclear cells. The patient was diagnosed with IIH and commenced acetazolamide. The follow-up MRI after 6 weeks revealed a complete disappearance of the CLOCC. Conclusion CLOCC, although very rare, could be present after an increase in the CSF pressure in patients with IIH. The lesion was restricted to the splenium and reversible after controlling the CSF pressure. Its presence could be associated with good prognosis.